1999
DOI: 10.1101/gad.13.8.978
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell hyperplasia and tumors in transgenic mice expressing a naturally occurring mutant NF2 protein

Abstract: Specific mutations in some tumor suppressor genes such as p53 can act in a dominant fashion. We tested whether this mechanism may also apply for the neurofibromatosis type-2 gene (NF2) which, when mutated, leads to schwannoma development. Transgenic mice were generated that express, in Schwann cells, mutant NF2 proteins prototypic of natural mutants observed in humans. Mice expressing a NF2 protein with an interstitial deletion in the amino-terminal domain showed high prevalence of Schwann cell-derived tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(148 citation statements)
references
References 32 publications
4
140
0
4
Order By: Relevance
“…Remarkably, vascular endothelial growth factor (VEGF) levels are significantly higher in pleural effusions secondary to mesothelioma in comparison with nonmalignant effusions (Zebrowski et al, 1999), and mesothelial cells and malignant mesothelioma cells have been reported as a source of VEGF (Lee et al, 2002). Heterozygous mutant Nf2 mice mainly develop osteogenic tumours (McClatchey et al, 1998) and only one mesothelioma was observed in a group of 16 Nf2 KO3/ þ mice (Giovannini et al, 2000). All tumour types found in these mice showed loss of the WT Nf2 allele.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, vascular endothelial growth factor (VEGF) levels are significantly higher in pleural effusions secondary to mesothelioma in comparison with nonmalignant effusions (Zebrowski et al, 1999), and mesothelial cells and malignant mesothelioma cells have been reported as a source of VEGF (Lee et al, 2002). Heterozygous mutant Nf2 mice mainly develop osteogenic tumours (McClatchey et al, 1998) and only one mesothelioma was observed in a group of 16 Nf2 KO3/ þ mice (Giovannini et al, 2000). All tumour types found in these mice showed loss of the WT Nf2 allele.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, in the first model, the floxed Nf2 gene was conditionally inactivated in SCs in vivo by tissue-specific expression of the Cre recombinase under the control of the P0 promoter (Giovannini et al, 2000). In the second model, SCspecific P0 promoter was used to drive the expression of a dominant negative mutant merlin (Sch-D39-121) (Giovannini et al, 1999). This model was used for experiments involving extracts from sciatic nerves.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…CD44 and ezrin play important roles in promoting tumor metastasis (Yu et al, 1997;Stamenkovic 1999, 2000;Yu et al, 2004;Khanna et al, 2001Khanna et al, , 2004, whereas merlin acts as a tumor suppressor (Rouleau et al, 1993;Trofatter et al, 1993;Lutchman and Rouleau, 1995;Sherman et al, 1997;McClatchey et al, 1998;Giovannini et al, 1999Giovannini et al, , 2000. Thus far, the functional relationship between CD44 and merlin and the manner in which CD44 affects the tumor-suppressing activity of merlin have not been established.…”
Section: Increased Expression Of Merlin Inhibits the Binding Of Fluormentioning
confidence: 99%